2020
DOI: 10.1111/ane.13354
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and lockdown: A survey of patients normally attending a Spanish centre

Abstract: Lockdown due to SARS-CoV-2, which lasted ten weeks in Spain, from 15 March to 25 May 2020, proved to be a physical and psychological challenge for the general population 1. Patients with chronic disorders have experienced special difficulties, even when their disease per se does not put them at significant risk for infection 2. We aimed to find out the effect of the lockdown on our patients with chronic (often drug resistant) epilepsy (PWE), and the possible changes in seizure frequency and severity, mood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
5
18
0
Order By: Relevance
“…According to our results, seizure frequency remained stable during the COVID‐19 pandemic, confirming previous reports 26‐28 . PWE presented no problems acquiring their medication, what has been reported in few patients due to expired prescription or unavailability 27 . Interestingly, no concerns about access to medication prescriptions have been found in remote interviews 29 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to our results, seizure frequency remained stable during the COVID‐19 pandemic, confirming previous reports 26‐28 . PWE presented no problems acquiring their medication, what has been reported in few patients due to expired prescription or unavailability 27 . Interestingly, no concerns about access to medication prescriptions have been found in remote interviews 29 …”
Section: Discussionsupporting
confidence: 90%
“…Higher NDDI‐E scores in PWE (whole sample) were associated with higher seizure frequency. Higher levels of depression were found in PWE at early stages of the confinement, 27 but without standardized measurement tools. Our results show that higher medium‐term NDDI‐E scores are associated with seizure frequency.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Half reported anxiety or depression, and 25% increased behavioral disorders. In agreement with the current study, the investigators concluded that seizure frequency and severity remained unchanged in most patients during the lockdown [14].…”
Section: Discussionsupporting
confidence: 91%
“…Tertiary hospitals in Spain have adapted care protocols and procedures in many areas and prioritized the use of remote monitoring for patients with chronic disease. 11 Spanish studies of the impact of the pandemic and lockdown measures in the setting of epilepsy have mainly identified collateral effects, 12,13 although one recent study described a higher incidence of COVID-19 in patients with epilepsy than in those without, probably because of the higher proportion of dependent and institutionalized patients in this population. 14 A previous cross-sectional survey-based study by our group analyzing the short-term effects of the COVID-19 pandemic on epilepsy patients from a tertiary hospital in Barcelona, Spain, showed emerging lockdown-related symptoms such as anxiety and depression in addition to sleep disturbances and reduced family income.…”
Section: Introductionmentioning
confidence: 99%